Induction of Pyroptosis in Renal Tubular Epithelial Cells Using High Glucose - Liu, Yinghong; He, Mingyue; Xiong, Hao; Yuan, Fang (Frontiers in Medicine, 2022)
Background: The micro-inflammatory state is important for the occurrence of diabetic kidney disease (DKD). Here, we aimed to explore the expression of pyroptosis related indicators and ultrastructural characteristics in DKD ,and investigate pyroptosis in renal tubular epithelial cells induced by high glucose. Methods: Immunohistochemistry was used to detect expression of the inflammation-related protein NOD-like receptor protein 3 (NLRP3) and pyroptosis key protein gasmedermin D (GSDMD) in kidney tissues of DKD patients. HK-2 cells were cultured in vitro and stimulated with different concentrations of glucose .The changes in HK-2 cell ultrastructure were observed using electronmicroscopy, and western blotting was used to detect NLRP3, caspase-1 p20, GSDMD-N, interleukin (IL)-1β, and IL-18 expression. Results: NLRP3 and GSDMD expression in kidney tissues of DKD patients was higher than that in control subjects.Further, GSDMD expression was positively correlated with that of NLRP3 (r = 0.847, P = 0.02). After stimulating HK-2 cells for 24 h with different glucose concentrations, compared with the control group, the 15 mmol/L and 30 mmol/L glucose groups showed typical ultrastructural changes of pyroptosis. The protein expression of NLRP3, caspase-1 p20, GSDMD-N, IL-1β, and IL-18 expression in high glucose increased significantly compared with the control group, and was glucose-concentration-dependent. Conclusion: High glucose can activate inflammasome , cause inflammatory cytokines release, and induce pyroptosis in HK-2 cells . NLRP3-caspase-1 may be involved in GSDMD-mediated pyroptosis. This study shows a novel relationship between glucose concentration and pyroptosis, which can be studied further to design better therapies for patients with DKD.